Social Capital in Cross-Sector Collaboration to Address Stunting: Rumah Pelita Case Study - Cendikia Nabila Ikhsani; Fadly Husein (Unnes Political Science Journal, 2025)
Stunting cannot be addressed solely through technical approaches, but requires structured and socially-based cross-sectoral collaboration. This study aims to analyze the forms of institutional collaboration and the role of social capital in supporting the effectiveness of Rumah Pelita in Semarang City, an intersectoral daycare service that focuses on restoring the nutrition and development of stunted children. This research uses a qualitative method with a case study approach through in-depth interviews, participatory observation, and documentation. The results show that Rumah Pelita's success in reducing the prevalence of stunting by 50-60% is influenced by the strength of social networks between agencies, parents' trust in caregivers, and collective work norms. The program integrates nutritional interventions, child development stimulation, parenting classes, and intensive monitoring. These findings reinforce the relevance of Putnam's social capital theory in explaining how networks, trust and social norms can strengthen cross-sectoral cooperation. In conclusion, Rumah Pelita can be used as a replication model for collaboration-based stunting interventions in other urban areas, as well as making a theoretical contribution to strengthening the concept of social capital in public health policy.